2017
DOI: 10.1186/s12951-017-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic investigation exploring the differential transfection efficiencies between the easy-to-transfect SK-BR3 and difficult-to-transfect CT26 cell lines

Abstract: BackgroundGold–polyamidoamine (AuPAMAM) has previously been shown to successfully transfect cells with high efficiency. However, we have observed that certain cell types are more amenable to Au–PAMAM transfection than others. Here we utilized two representative cell lines—a “difficult to transfect” CT26 cell line and an “easy to transfect” SK-BR3 cell line—and attempted to determine the underlying mechanism for differential transfection in both cell types. Using a commonly established poly-cationic polymer sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…36 Differences in the dynamics of trafficking have been shown in a recent study that also identified CT26.WT mouse line as a low protein expressor compared with breast cancer SK-BR3 cells following transfection with DNA plasmid polyplexes composed of either polyethyleneimine (PEI) or polyamidoamine gold. 37 A high initial polyplex uptake rate was identified as a determining factor for transfection efficiency, similar to what we observe here with an LNP delivering mRNA. The data also highlights, without comment, juxtanuclear polyplexes in SKBR3 cells but scattered localisation in CT26.WT cells.…”
Section: Discussionsupporting
confidence: 84%
“…36 Differences in the dynamics of trafficking have been shown in a recent study that also identified CT26.WT mouse line as a low protein expressor compared with breast cancer SK-BR3 cells following transfection with DNA plasmid polyplexes composed of either polyethyleneimine (PEI) or polyamidoamine gold. 37 A high initial polyplex uptake rate was identified as a determining factor for transfection efficiency, similar to what we observe here with an LNP delivering mRNA. The data also highlights, without comment, juxtanuclear polyplexes in SKBR3 cells but scattered localisation in CT26.WT cells.…”
Section: Discussionsupporting
confidence: 84%
“…CT26 is known to be extremely difficult to transfect using ionizable lipids, believed to be due, in part, to a defective endolysosomal system and thus represents a robust challenge to the developed system. , As shown in Supplementary Figure 5, we observe no significant reduction in tumor size or improved mouse survival. This suggests that efficacy may be limited to the highly transfectable cell lines such as B16F10.…”
Section: Resultsmentioning
confidence: 68%
“…Efficient cellular uptake is a crucial step for achieving high transfection efficiency [ 32 ]. 293TN cells were transfected by the synthesized gene vectors encapsulating Cy5-labelled pDNA for 6 h. The results in Figure 7B showed that the uptake efficiency for all gene vectors reached almost 95% without significant difference.…”
Section: Resultsmentioning
confidence: 99%